The Determinants of Learning Motivation among Students in Islamic Education: Implementation of the Merdeka Curriculum and Learning Facilities - Nia Trisnawati; Amie Primarni; Ernawati Ernawati (Jurnal Dirosah Islamiyah, 2026)
Learning motivation plays a crucial role in determining the effectiveness of learning processes, particularly in Islamic Education, which emphasizes cognitive, affective, and character development. In response to recent educational reforms in Indonesia, the implementation of the Merdeka Curriculum and the availability of learning facilities are expected to influence students’ learning motivation. This study aims to examine the determinants of students’ learning motivation in Islamic Education through the implementation of the Merdeka Curriculum and learning facilities, both partially and simultaneously. Employing a quantitative correlational design, data were collected from students participating in Islamic Education learning in institutions implementing the Merdeka Curriculum using a structured questionnaire. The data were analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that the implementation of the Merdeka Curriculum and learning facilities have significant positive effects on students’ learning motivation, both individually and collectively. These findings demonstrate that curriculum flexibility, learner autonomy, and adequate learning environments contribute to higher levels of student motivation. The originality of this study lies in its integrated analysis of curriculum implementation and learning facilities as key determinants of learning motivation in the context of Islamic Education, an area that has received limited empirical attention. In conclusion, enhancing students’ learning motivation in Islamic Education requires a synergistic approach that combines effective curriculum implementation with adequate and well-utilized learning facilities.